Cardiorenal syndrome in patients with heart failure as a stage of the cardiorenal continuum (part 2): prognosis, prevention and treatment - E. V. Reznik; I. G. Nikitin (SINAPS LLC, 2019)
Cardiorenal syndrome in patients with heart failure is a regular link in the chain of cardiorenal continuum. Physicians of various specialties may encounter patients with cardiorenal syndrome: general practitioners, cardiologists, nephrologists, resuscitators, anesthetists, cardiac surgeons, etc. The currently definition, classification, pathogenesis, diagnosis and epidemiology of cardiorenal syndrome in patients with heart failure were presented in first part of our review. In the second part, prognosis, approaches to the prevention and treatment of cardiorenal syndrome in patients with heart failure are discussed. They include the treatment of cardiovascular pathology and heart failure in accordance with current guidelines for the prevention of episodes of acute and decompensated chronic heart failure; diet; smoking cessation, alcohol, nephrotoxic substances; body weight, blood pressure and glycemia control; angiotensin converting enzyme inhibitors, angiotensin receptor antagonists or angiotensin receptors and neprilisin inhibitors (ARNI), statins; reducing of the abdominal pressure and others. It is necessary to develop and introduce new approaches to nephroprotection in patients with cardiorenal syndrome, which is possible with the joint work of a multidisciplinary team.